Prior disinfestation of irrigated rice seeds under laboratory conditions favors expression of physiological potential - Scheidt, Bruno Tabarelli; Garcia, Jaquelini; Casa, Ricardo Trezzi; Coelho, Cileide Maria Medeiros; Berghetti, Juliano (Revista de Ciências Agroveterinárias, 2020)
The purpose of this study was to analyze prior seed disinfestation of irrigated rice seeds with sodium hypochlorite and its effect on physiological quality. The experiment was conducted in the seed analysis laboratory of Santa Catarina State University (UDESC). Twenty-four (four per cultivar) seed lots of the cultivars SCSBRS Tio Taka, Epagri 109, SCS116 Satoru, SCS118 Marquês, SCS121 CL, and SCS122 Miura, produced in the Upper Itajaí Valley in the 2016/2017 season, were used in a completely randomized experimental design with four replications. Germination and vigor tests were performed with and without disinfestation seeds. For the germination test with disinfected seeds, there was a higher percentage of normal seedlings and a smaller number of abnormal seedlings and dead seeds. There was significant decrease in vigor without prior seed disinfestation. The fungi that infested the seeds caused an increase in the percentage of abnormal seedlings and dead seeds. Seed disinfestation prior to physiological test positively affects the results regarding the physiological quality of irrigated rice seeds.